Preliminary Study: Profile of Students’ Interpretation Skills on the Topic of Kinematics - Yennita Yennita; Zulirfan Zulirfan; Mitri Irianti; M Idris Tukan; Talia Ananda; Khoirul Ahlun Naza (Postgraduate, University of Mataram, 2023)
A graph is a type of representation that is useful in summarizing data, and processing and interpreting new information from complex data. One of the reasons why it is important to understand graphical representation is because graphs can provide quantitative information that is easy to understand. Kinematics is the science of dealing with the movement of an object. Learning can not be separated from pictures and graphics. This study aims to see the initial ability of prospective physics teacher students in interpreting graphs. This mapping is useful for making policy plans for lecturers in planning future physics lessons. This type of research is descriptive research involving 79 respondents. Data collection is done by giving a graph interpretation ability test which consists of 3 indicators, namely graphs interpretation to mathematics, graphs interpretation to descriptions, and graph interpretation to images. From the results of data analysis using descriptive statistics, it was found that the student's ability to interpret graphs was in a low category. This gives information to lecturers that training and strengthening graphic interpretation skills still need to be a concern